Hundred-meter freestyle-specific training using various interval training set designs
The aerobic:anaerobic contribution to 100 m swimming is 40:60. This balance of energy demands can be provided by including the following sets in training: 10 x 50 m on 1:4 (best) or 1:8 work:recovery ratios and 5 x 100 m on 1:8 work:recovery ratio. The pace for each of the 50 or 100 m repeats should be as fast as possible. Implications: A key consideration for sprint training is not tolerance of lactate or ability to maintain high lactate values but rather, the ability to always deliver energy at very high rates that result from specific energy adaptations. The recommended sets match the energy demands and hone the pace required for a maximum 100 m swim. By training the appropriate movement patterns in harmony with the correct balance of energy supply, the training effect will be a very specific form of adaptation that will transfer to the competitive 100 m event. (ICAR 1990-91 Report)